2021
DOI: 10.1007/s00420-021-01738-3
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to cisplatin in the operating room during hyperthermic intrathoracic chemotherapy

Abstract: Purpose Hyperthermic intrathoracic chemotherapy (HITOC) is an additive, intraoperative treatment for selected malignant pleural tumors. To improve local tumor control, the thoracic cavity is perfused with a cisplatin-containing solution after surgical cytoreduction. Since cisplatin is probably carcinogenic to humans, potential contamination of surfaces and pathways of exposure should be systematically investigated to enable risk assessments for medical staff and thus derive specific recommendatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…In a previous study conducted by our working group, we measured the amount of cisplatin on the surface of the surgeon's and the perfusionist's hand gloves, as well as on the display of the perfusion system, on the floor in the operating theatre, and the inside of the endobronchial tube. The highest burden of cisplatin-although very low generally speaking-was detected on the surgeon's hand gloves (median 1.73 pg cisplatin/cm 2 ), followed by the perfusionist's hand gloves (0.69 pg cisplatin/cm 2 ) and the display of the perfusion system (0.57 pg cisplatin/cm 2 ) [19]. In a comparable study focusing on HIPEC (hyperthermic intraperitoneal chemotherapy), the median cisplatin contamination on surfaces was 2.31 pg cisplatin/cm 2 (the platinum level multiplied by 1.54 for the cisplatin level), and thereby three times higher than that on the highest contaminated area in our study.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In a previous study conducted by our working group, we measured the amount of cisplatin on the surface of the surgeon's and the perfusionist's hand gloves, as well as on the display of the perfusion system, on the floor in the operating theatre, and the inside of the endobronchial tube. The highest burden of cisplatin-although very low generally speaking-was detected on the surgeon's hand gloves (median 1.73 pg cisplatin/cm 2 ), followed by the perfusionist's hand gloves (0.69 pg cisplatin/cm 2 ) and the display of the perfusion system (0.57 pg cisplatin/cm 2 ) [19]. In a comparable study focusing on HIPEC (hyperthermic intraperitoneal chemotherapy), the median cisplatin contamination on surfaces was 2.31 pg cisplatin/cm 2 (the platinum level multiplied by 1.54 for the cisplatin level), and thereby three times higher than that on the highest contaminated area in our study.…”
Section: Discussionmentioning
confidence: 91%
“…During and after HITOC, there are several possibilities for staff to come into contact with the cisplatin excreted by the patient: via urine (while emptying the urine catheter bag), bronchial secretion (while coughing, performing oral hygiene, or endotracheal suction), pleural fluid in the thoracic drainages, and pleura fluid running aside the drainage out of the wound. Thus, unintended contact with cisplatin and other cytostatic drugs by the surgical or nursing staff should be avoided, and special safety actions should be applied, such as the use of cytostatic hand gloves, fluid-repellent surgical gowns, safety glasses with side protection, and the signposting of the operation theatre and the immediate surroundings of the patient's bed [19]. However, cisplatin exposure during and after HITOC has not yet been fully investigated, especially with regard to occupational safety.…”
Section: Of 12mentioning
confidence: 99%
“…The USP 19 and Oncology Nursing Society 23 recommend use of at least an N95 respirator because of the risk of exposure to aerosolized hazardous medications during handling. However, a study on procedures involving hyperthermic intrathoracic chemotherapy (HITOC) 24 and pressurized intraperitoneal aerosol chemotherapy (PIPAC) techniques 25 found that the risk of air contamination during these procedures was low.…”
Section: Hazardous Medicationsmentioning
confidence: 99%
“…Moreover, emerging evidence reveals cisplatin can be highly detrimental to healthcare workers, who are daily exposed during the preparation and/or administration of chemotherapy [ 12 , 13 , 14 ]. The continuous work-related exposure to cisplatin might cause various organ damage and severe renal toxicity [ 13 , 15 , 16 , 17 , 18 ]. Other chronic effects linked with exposure to antineoplastic drugs, including spontaneous abortion and congenital anomalies [ 18 , 19 , 20 , 21 ], have also been reported.…”
Section: Introductionmentioning
confidence: 99%